2019
DOI: 10.1177/0748233719842752
|View full text |Cite
|
Sign up to set email alerts
|

Chemical- and microbial-enhanced phytoremediation of cadmium-contaminated calcareous soil by maize

Abstract: Phytoremediation is an appropriate technology used to remove pollutants from environment components. A greenhouse trial was conducted to test the hypothesis that application of surfactant levels and inoculation with Pseudomonas fluorescens bacterium and/or Piriformospora indica fungus enhances the phytoremediation of cadmium (Cd). Maize seeds were sown in Cd-polluted soil, and after 2 months Cd status in plant tissues and Cd phytoremediation criteria was determined. Results showed that application of surfactan… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 13 publications
(5 citation statements)
references
References 31 publications
0
5
0
Order By: Relevance
“…In functional and growth-promotion aspects, P. indica can promote plant growth [30], and the absorption and utilization of nutrients, while improving the plants' nutritional value [28]. This effect has been seen in corn [27] and wheat [31]. Inoculation of P. indica increased chlorophyll content and tolerance of alfalfa in the Phenanthrene and Cadmium co-contaminated soil [16].…”
Section: Introductionmentioning
confidence: 97%
See 1 more Smart Citation
“…In functional and growth-promotion aspects, P. indica can promote plant growth [30], and the absorption and utilization of nutrients, while improving the plants' nutritional value [28]. This effect has been seen in corn [27] and wheat [31]. Inoculation of P. indica increased chlorophyll content and tolerance of alfalfa in the Phenanthrene and Cadmium co-contaminated soil [16].…”
Section: Introductionmentioning
confidence: 97%
“…It can also enhance the expression of antioxidant system components and stress-related genes [20][21][22] and induce plant stress resistance [23][24][25]. P. indica has been reported to enhance the activity of antioxidant enzyme systems in barley [26], corn [27], and banyan [28]. In addition, under both mycorrhizal association and stresses, the content of proline involved in the resistance to oxidative stress of cells also increased [29].…”
Section: Introductionmentioning
confidence: 99%
“…Wang et al resulted that PGPM inoculants enhanced oilseed Cd concentration and Cd phytoextraction efficiency, and the soil Cd removal rate of PGPM inoculated plants was 2.44 times higher than that of non-inoculated plants [ 54 ]. Asilian et al inoculated Piriformospora indica increased plant root Cd concentration and the uptake of maize [ 55 ]. Chen et al reported that inoculating Sphingomonas SaMR12 significantly increased Zn uptake by S. alfredii was close to 23 fold [ 56 ].…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, the same fungal species showed antagonistic effects on different plants, decreasing or increasing metal accumulation. This is the case for Piriformospora indica, which increases wheat but decreases maize metal uptake (Asilian et al, 2019;Shahabivand et al, 2012), or Trichoderma asperellum, which has no effect on Lactuca serriola metal uptake and translocation but shows a negative effect on onion and Suaeda salsa metal uptake and translocation (Li et al, 2019;Téllez-Vargas et al, 2017;Ważny 2018). It has been shown for AMF that fungal tolerance may vary individually, with local adaptation to metal contamination at the intraspecific level (Colpaert et al, 2004;Jourand et al, 2010;Vallino et al, 2011).…”
Section: Mte Avoidance or Accumulationmentioning
confidence: 99%